Study on the Taxonomy of Genus Favia (Oken, 1815) at the Reef Flats of Kampung Ambong Village in Likupang Timur District, Minahasa Utara - Reskiwati, .; Lalamentik, Laurentius X. T.; Rembet, Unstain N. W. J (Sam Ratulangi University, 2018)
Coral reefs in the world occupy around 250.000 km2 of coastal areas and provide habitats for approximately 25 % of marine species. Reefs are usually reognise as marine rain forest (Knowlton et al., 2010 in Andi Haerul, 2014). Indonesia has a high level of hard corals diversity, and, at least 80 genera consist of 74 % of 800 coral spesies of the world could be found here.Favia (Oken, 1815) is one genus of Faviidae. Faviidae is one of the largest coral family, after Acroporidae. Coral species of Faviidae live in a colony. Generally, the main characteristic of Favia has plocoid shape corallite. Data collection has been conducted on reef flats of Kampung ambong Village in Likupang Timur District of Minahasa Utara Regency. Visual survey method was done at 3 – 5 meters depths during high tide rising. This research was focused on genus Favia (Oken, 1815) of Faviidae family.Five species of hard corals of genus Favia were founded in this study,i.e Favia speciosa (Dana, 1846), Favia favus (Forskål, 1775), Favia truncatus (Veron, 2000), Favia pallida (Dana, 1846) dan Favia matthaii (Vaughan, 1918). These species have similar characteristics in some parts, i.e septum, corallite form and corralite diameter.Keywords: Taxonomy, Hard Coral, Favia (Oken, 1815) ABSTRAK Terumbu karang di dunia memiliki luas sekitar 250.000 km2 dan merupakan tempat tinggal bagi 25% spesies laut sehingga terumbu karang disebut juga rain forest laut (Knowlton et al. 2010 dalam Andi Haerul, 2014). Indonesia memiliki tingkat keanekaragaman spesies karang yang tinggi yaitu kurang lebih 80 genera meliputi 74% dari 800 spesies yang ada di dunia.Karang Favia (Oken, 1815) merupakan salah satu genus dari famili karang Faviidae yang menjadi salah satu famili terbesar setelah Acroporidae. Spesies dari famili Faviidae hidup secara berkoloni. Ciri-ciri umum dari genus ini adalah bentuk koralit plocoid. Pengambilan data dilakukan di Desa Kampung Ambong Kecamatan Likupang Timur, Minahasa Utara. Metode yang digunakan adalah metode survei jelajah pada kedalaman 3-5 meter pada saat terjadi pasang naik. Karang yang diamati adalah famili Faviidae, genus Favia (Oken, 1815).Pada penelitian ini ditemukan lima spesies karang genus Favia, yaitu Favia speciosa (Dana, 1846), Favia favus (Forskål, 1775), Favia truncatus (Veron, 2000), Favia pallida (Dana, 1846) dan Favia matthaii (Vaughan, 1918). Spesies ini memiliki karakteristik yang hampir mirip pada beberapa bagian seperti septa, bentuk koralit, serta diameter koralit.Kata Kunci: Taksonomi, Karang Batu, Favia (Oken, 1815)